Requirements engineering of an Online Quiz Systems for SK Serdang using Viewpoint-Oriented Requirements Definition (VORD) method / Nur Syuhada Irwani Wahab - Wahab, Nur Syuhada Irwani (2015)
Online Quiz System has been proposed by Sekolah Kebangsaan Serdang which is located at Dungun, Terengganu. The Online Quiz Systems focuses on Mathematics subject. The main problem to be solved is the student record is hard to keep and doing the quiz manually is less interested among students. The current business of the school is doing manually and the result keep in the log book. This research project is to gather and analyze the user requirement for Online Quiz Systems using the Viewpoint Oriented Requirements Definition (VORD) method. While there are three objectives which are to identify the requirements for Online Quiz Systems using VORD, to develop a user interface prototype of the Online Quiz Systems based on the identified requirements and to validate the requirements using the prototype. In gathering the requirements, VORD is applied. VORD is a method to tackle the requirement engineering from a viewpoint level. It detects the needs of different categories of users and identifies the services that they expect. Three steps are involved in this method which is viewpoint identification and structuring, viewpoint documentation and viewpoint analysis and specification. Once the requirements has been gathered and analyzed, the prototype will be developed based on the correct requirements. After developed the prototype, the validation of the requirements is next. The users will be given the requirements checklist to validate the user interface prototype. Requirements checklist is the list of services that are user expects. As a result, the users are satisfied with the developed prototype which means the VORD method is suitable method in gathering the correct user requirements in requirements engineering. Since this project is focuses on the requirement engineering of Online Quiz Systems, it is highly recommend to developer would continue this project in the next phase of System Development Life Cycle (SDLC) where the Software Requirement Specification (SRS) can be as reference for the development.